Aplikasi bakteri asam laktat (BAL) untuk meningkatkan keamanan mikrobiologis terhadap Staphylococcus aureus pada proses olah minimal buah apel Malang (Malus sylvestris Mill.) - Rahmadi, Anton (Jurusan Teknologi Hasil Pertanian Universitas Mulawarman, 2005)
Minimally processed apple usually came from partially-broken apple with some parts are still in very good condition. Minimally processed fruits are perishable foods due to quality degradation caused by microorganism activity. Main purpose of this research was to study the application of LAB culture in minimally processed apple fruit of Malang in order to increase safety against Staphylococcus aureus. Malang apple was used in this research while age of ripe 4.5 months and weight of around 90-100 grams. Lactic acid bacteria used were Lactobacillus brevis, and three strains of L. plantarum. Steps of this research are selection of potential LAB strains using well diffusion method, determining LAB concentration and soaking time, study of minimally processed apple shelf life and total acid titration. pH and total LAB colonies (Total Plate Count) in MRS agar medium, as well as total Staphylococcus aureus. Best inhibition-zone of S. aureus are was resulted from strain of L. brevis AE 1.6 (14.33mm). Optimum concentration to inhibit pathogenic bacteria is 10^6 cfu per mL with 30 minutes of soaking. Pathogenic bacteria life colonies decreased for 1 to 2 of log unit following soaking in optimal LAB concentration. LAB application in minimally processed apple did succeeded to increase safety against pathogens specially S. aureus. Shelf life could be extended up to 12 days with S. aureus life colonies not more than 100 cfu per g.